2010
DOI: 10.2353/ajpath.2010.091108
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke-Related Hydroquinone Induces Filamentous Actin Reorganization and Heat Shock Protein 27 Phosphorylation through p38 and Extracellular Signal-Regulated Kinase 1/2 in Retinal Pigment Epithelium

Abstract: Retinal pigment epithelium (RPE)-derived membranous debris named blebs, may accumulate and contribute to sub-RPE deposit formation, which is the earliest sign of age-related macular degeneration (AMD). Oxidative injury to the RPE might play a significant role in AMD. However, the underlying mechanisms are unknown. We previously reported that hydroquinone (HQ), a major pro-oxidant in cigarette smoke, foodstuff, and atmospheric pollutants, induces actin rearrangement and membrane blebbing in RPE cells as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
(68 reference statements)
3
36
1
1
Order By: Relevance
“…Rearrangement of filamentous actin in cells treated with nonlethal doses of HQ has been reported. In retinal epithelium cells nonlethal oxidative injury with HQ induced blebbing and formation of actin aggregates mediated by phosporylation of Hsp27 [19,20]. Even if HQ has dramatic effects on microtubule organization and induces a loss of actin filaments in the present study, we cannot completely exclude that HQ exerts a direct effect on the molecular motors responsible for aggregation and dispersion.…”
Section: Discussioncontrasting
confidence: 40%
“…Rearrangement of filamentous actin in cells treated with nonlethal doses of HQ has been reported. In retinal epithelium cells nonlethal oxidative injury with HQ induced blebbing and formation of actin aggregates mediated by phosporylation of Hsp27 [19,20]. Even if HQ has dramatic effects on microtubule organization and induces a loss of actin filaments in the present study, we cannot completely exclude that HQ exerts a direct effect on the molecular motors responsible for aggregation and dispersion.…”
Section: Discussioncontrasting
confidence: 40%
“…[28][29][30][31][32] HQ has also been found in vitro and in animal models to affect gene expression of oxidative stress-related mediators and genes related to AMD pathogenesis. [33][34][35] HQ can reduce the activity of matrix metalloproteinase 2 (MMP-2) in vitro, 33 downregulate the monocyte chemoattractant protein 1 (MCP1), upregulate vascular endothelial growth factor (VEGF) and pigment epithelium-derived factor (PEDF) expression in vitro and in mice 34 , and upregulate the expression of heat shock protein 27 (Hsp-27) in mice and in vitro models. 35 In a rat model, it has been reported that after exposition to cigarette smoke or HQ supplemented in the rat's diet, the trial animals developed sub RPE deposits and Bruch's membrane thickening and deposits.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of evidence suggests cross-talk between p38 and ERK MAPK cascades in a variety of cells 79 -82 including human RPE cells, as recently demonstrated. 83 Evidence was reported that p38 MAPK exerts a tonic inhibition on the ERK pathway that positively modulates p38 signaling under basal conditions in ARPE-19 cells. 83 The signaling events responsible for such cross-talk between p38 and ERK signaling cascades are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…83 Evidence was reported that p38 MAPK exerts a tonic inhibition on the ERK pathway that positively modulates p38 signaling under basal conditions in ARPE-19 cells. 83 The signaling events responsible for such cross-talk between p38 and ERK signaling cascades are poorly understood. Cross-talk between parallel pathways of the MAPK cascades depends on a complex interplay involving kinases and phosphatases.…”
Section: Discussionmentioning
confidence: 99%